Stability of Cocaine, Opiates, and Metabolites in Dried Saliva Spots - Almeida, Ema (2022)
Funding: LA/P/0140/2020 (i4HB) being carried out by National Funds by Foundation for Science and Technology (FCT) and co-financed by community funds. T. Rosado thanks the Centre for Competences in Cloud Computing for the scholarship with reference C4_WP2.6_M1—Bioinformatics; UBIMEDICAL— CENTER-01-0145-FEDER-000019-C4—Centre for Competences in Cloud Computing, European Regional Development Fund (FEDER) and Centro Regional Operational Program (Centro 2020). S. Soares and J. Gonçalves acknowledge the FCT for the PhD fellowships with references SFRH BD/148753/2019. Publisher Copyright: © 2022 by the authors. Licensee MDPI, Basel, Switzerland.